Novel Smart Fuzzy Controller Based Separation Efficiency Model for Centrifugation - M. S. Salim; Naseer Sabri; Noaman M. Noaman; S. Fouad (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
This paper is under in-depth investigation due to suspicion of possible plagiarism on a high similarity indexIn biomedical laboratories, to get surely separation efficiency of liquids using currently centrifuge devices, centrifugation process must take not less than 10 minutes at 3000 rpm of sample rotation. An intelligent fuzzy controller for laboratory centrifuge device based on separation efficiency model is produced.  The separation efficiency model is optimizing the time of centrifugation. The new controller programmed with separation efficiency model have many objectives such as high separation efficiency, decrease blood test period, low cost and device power consumption are achieved. In addition, increases the reliability for centrifuge device to estimate the centrifugation period for wide range of predefined separation efficiency, and then, the power consumption of specific separation efficiency for any centrifuge device wattage can be estimate.  The new Fuzzy Logic Controller of centrifuge device has successfully save 18kW.h monthly for 100 daily time device operation.